Sistem Diagnosis Penyakit Penglihatan Kabur Pada Mata Menggunakan Metode AHP-SAW - Mochammad Faizal Satria Rahman; Nurul Hidayat; Ratih Kartika Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Blurred vision sickness is an eye-attacking disease which has a high rate of cases in Indonesia. The disease is also difficult to detect visually. In many cases, this disease is detected when the symptom is already severe. Patients with this disease are usually not aware of blurred vision symptom. Therefore it needs expert diagnosis to understand this disease. On the other hand, limited number of eye experts in Indonesia is also problem which has to be addressed. Those problems can be solved by establishing an expert system of blurred vision diagnosis. Expert systems are part of artificial intelligence which contains expert knowledge and experience incorporated into a particular area of knowledge to solve specific problems. Method of Analytic Hierarchy Process-Simple Additive Weighting (AHP-SAW) is kind of method which applied to overcome the problem of identifying criterion with measuring data qualitatively and quantitatively. Based on the test data which used in this study, system succeed to diagnosis of blurred vision sickness with 87% of accuracy.